2022
DOI: 10.1186/s12903-022-02298-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of giomer- and resin-based fissure sealants on permanent molars affected by molar-incisor hypomineralization: a randomized clinical trial

Abstract: Background Molar-incisor hypomineralization (MIH) is a common condition among children that significantly increases the risk of caries. The objective of this research was to evaluate the clinical success of giomer- and conventional resin-based sealants applied on first permanent molars (FPMs) affected by MIH. Methods One-hundred FPMs with MIH which were indicated for non-invasive fissure sealant were selected in 39 children, aged 6–12 years. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…For molars, documented therapeutic options include infiltration of lesions with resins, glass ionomer or resin-modified glass ionomer restorations, preformed stainless steel crowns, and even planned extraction in severe cases for children aged 8 to 10 years, followed by orthodontic treatment. However, a recent randomized clinical trial [ 22 ] found that conventional resin-based sealants in permanent first molars have better long-term clinical performance than ionomer sealants with self-etch adhesive. This may be due to etching failure in teeth affected by MIH.…”
Section: Discussionmentioning
confidence: 99%
“…For molars, documented therapeutic options include infiltration of lesions with resins, glass ionomer or resin-modified glass ionomer restorations, preformed stainless steel crowns, and even planned extraction in severe cases for children aged 8 to 10 years, followed by orthodontic treatment. However, a recent randomized clinical trial [ 22 ] found that conventional resin-based sealants in permanent first molars have better long-term clinical performance than ionomer sealants with self-etch adhesive. This may be due to etching failure in teeth affected by MIH.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the retention rates of dental sealants published in the past ten years (2012–2022). For resin sealant, the retention rate ranges from 11% to 89% at a 6-month follow-up ( 40 , 52 , 61 , 62 ); from 18 to 88% at a 12-month follow-up ( 26 , 45 , 47 , 49 51 , 55 , 58 – 60 , 65 , 67 ); from 24% to 70% at an 18-month follow-up ( 54 , 57 , 68 ); from 21% to 80% at a 24-month follow-up ( 44 , 46 , 48 , 63 , 64 , 66 ). Studies with longer follow-up periods were limited.…”
Section: Longevity Of Dental Sealantmentioning
confidence: 99%
“…Studies in other follow-up periods were limited. For hybrid sealant, the retention rates range from 8% to 26% at a 12-month follow-up ( 58 , 65 , 67 ). Studies with longer follow-up periods were limited.…”
Section: Longevity Of Dental Sealantmentioning
confidence: 99%
“…The teeth with Alpha and Bravo values are grouped in successful while the teeth with the value Charlie are divided into the group of unsuccessful cases [19]. The treated teeth were divided into groups according to the location (Mandibular-Maxillary) and the type of cavity (Class-1/Occlusal, Class-2, Class-3/Proximal).…”
Section: United States Public Health Service (Usphs) Criteriamentioning
confidence: 99%